Adaptive Material Design Supporting Personalized Education: Challenges and Opportunities - Akbar Maulana; Derine Yosando Wiyono (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Personalized education is an approach that tailors methods, pace, and learning content to the individual needs of students. Adaptive materials, as an essential component of personalized education, are designed to respond to the changing needs, interests, and abilities of students by dynamically adjusting learning content. This article aims to explore the concept of adaptive material design, discuss the challenges in its implementation, and identify emerging opportunities to support personalized education. Key challenges include the complexity of technology development, limited adaptability of content to the curriculum, and the digital infrastructure gap. On the other hand, advances in artificial intelligence (AI), machine learning, and data analytics present significant opportunities to enhance the effectiveness and accessibility of personalized education.